Local Partition in Rich Graphs - Freitas, Scott; Cao, Nan; Xia, Yinglong; Horng Polo Chau, Duen; Tong, Hanghang (International Conference on Big Data, 2018)
Local graph partitioning is a key graph mining tool that allows researchers to identify small groups of interrelated nodes (e.g., people) and their connective edges (e.g., interactions). As local graph partitioning focuses primarily on the graph structure (vertices and edges), it often fails to consider the additional information contained in the attributes. We propose a scalable algorithm to improve local graph partitioning by taking into account both the graph structure and attributes. Experimental results show that our proposed AttriPart algorithm finds up to 1.6× denser local partitions, while running approximately 43× faster than traditional local partitioning techniques (PageRank-Nibble).